On graded j-ideals over graded rings - Al-Shorman, Tamem; Bataineh, Malik; Celikel, Ece Yetkin; Çelikel, Ece Yetkin (KOREAN MATHEMATICAL SOC, 2023)
. The goal of this article is to present the graded J-ideals of G-graded rings which are extensions of J-ideals of commutative rings. A graded ideal P of a G-graded ring R is a graded J-ideal if whenever x, y & ISIN; h(R), if xy & ISIN; P and x & ISIN;̸ J(R), then y & ISIN; P, where h(R) and J(R) denote the set of all homogeneous elements and the Jacobson radical of R, respectively. Several characterizations and properties with supporting examples of the concept of graded J-ideals of graded rings are investigated.
Keywords: graded n-ideals; raded rings; Graded J-ideals